Management of portal hypertension before and after liver transplantation. Issue 1 (21st December 2017) - Unger, Lukas W.; Berlakovich, Gabriela A.; Trauner, Michael; Reiberger, Thomas
Abstract : Orthotopic liver transplantation (OLT) represents a curative treatment option for end‐stage liver disease (ESLD). Although epidemiology of ESLD has recently changed due to the rising prevalence of nonalcoholic fatty liver disease and the decreased burden of hepatitis C virus infections due to highly effective antiviral regimens, the management of portal hypertension (PHT) remains a clinical challenge in the pre‐ and post‐OLT setting. The measurement of the hepatic venous pressure gradient represents the most reliable but invasive tool for assessment of the severity of PHT. Although novel liver ultrasound and magnetic resonance–based elastography methods have been developed, their value to screen for liver fibrosis and PHT in transplanted patients remains to be established. Nonselective beta‐blockers represent the cornerstone of medical treatment of PHT, but more studies on their effects on clinical endpoints after OLT are needed. Statins are widely used to treat hyperlipidemia, which is a common condition after OLT. Although a growing body of evidence suggests that statins decrease portal pressure and PHT‐related complications in ESLD, studies on potential benefits of statins after OLT are lacking. Finally, transjugular intrahepatic portosystemic shunts (TIPS) are effective in decreasing PHT and seem to decrease mortality on the OLT waiting list. Moreover, TIPS does not have an impact on liver function nor complicate the transplant surgical procedures. TIPS may also be used after OLT, but the evidence is limited. In conclusion, whereas the management of PHT in patients with ESLD is based on strong evidence, further data on the value of noninvasive monitoring tools as well as on medical and invasive treatment options in the post‐OLT setting are needed to improve management strategies in patients with recurrent PHT after liver transplantation. Liver Transplantation 24 112–121 2018 AASLD.